Alguém me ouve?: Experiência de velhos/as atendidos pelo serviço de convivência e fortalecimento de vínculos (SCFV) - Chácara do idoso de Sorocaba-SP - Thomazini, Elisângela Maria (2023)
Population aging is a phenomenon observed worldwide. However, contrary to this process, studies indicate that this population segment needs to receive the necessary attention in contemporary society. The extension of life has brought aging into the public spotlight, demanding the reorganization of the government's agenda and investment in public policies focused on this demographic. In this scenario, Social Assistance Policy stands out as a social protection mechanism and guarantees citizenship rights. The objective of this dissertation is to understand old age based on the experiences of the elderly, how they feel listened to, their perception of aging, and the challenges and possibilities they face as rights holders. Through this listening process, the aim was also to analyze how they understand their rights in this relationship and whether they know the role of social assistance in guaranteeing those rights. For this purpose, this study employed thematic oral history as a methodology, guiding interviews with four users of the Elderly Farm in Sorocaba, where the Service of Coexistence and Strengthening of Bonds (SCFV) takes place. Through their narratives, the elderly expressed their experiences, revealing how much we still need to progress as a society to provide comprehensive listening to older individuals. The material produced will promote reflections on the topic of aging, contributing to the construction of a critical and transformative framework.